Kecantikan, Skincare, dan Validasi Sosial - Iftita, Nur (Universitas Muslim Maros, 2025)
Facial skincare has become a cultural practice that serves not only as a functional necessity but also as a means of seeking social validation. Although most research on beauty focuses on purchasing decisions and marketing effectiveness, the role of social validation in shaping consumer experiences and satisfaction with skincare products has not been widely explored, and this article fills this gap. Using a qualitative approach, this study involves ten informants consisting of two housewives, three content creators, two make up srtists and college students respectively, and a high school student. Their age ranges between 17 and 27 years, and they are active users of Bening's Skincare in Makassar. Data collection was conducted by combining observation on social media platforms and in-depth interviews. The study shows that consumer perceptions are formed through two main aspects: expectations influenced by visual testimonials on social media and interpersonal recommendations, and safety perceptions that become critical considerations, especially after the